Enhancing Data Privacy and Fraud Detection in the Takaful Industry through Digital Platforms and E-Knowledge Sharing: Moderating Role of AI Adoption - Qazi, Mansoor Ahmad; Md Husin, Maizaitulaidawati Binti (International Review of Management and Marketing, 2026)
This research explored the factors essential to data privacy and security in takaful institutions and proposed digital platforms (DPs) to enhance them, mediated by E-knowledge sharing. Moreover, the moderating role of AI adoption on the connection between E-knowledge sharing and data privacy and fraud detection has also been tested. The current study was conducted across various takaful (Islamic insurance) institutions in the United Arab Emirates (UAE) using a survey. Online questionnaire forms were used to collect data, which were subsequently analysed using statistical techniques, including correlation, partial least squares structural equation modelling, and bootstrapping, yielding several interesting results for the formulated hypotheses. The findings confirm the prediction that digital platforms can enhance data privacy and fraud detection. Moreover, the findings confirmed the mediating role of E-sharing in the direct effects of digital platforms, data privacy, and fraud detection. Finally, the findings revealed that AI adoption strengthens the connection between E-knowledge sharing and data privacy, as well as fraud detection.